Selective reduction in the expression of type‐1 metabotropic glutamate receptors in the hippocampus of adult rats born by caesarean section. Issue 4 (7th April 2021) - Zuena, Anna Rita; Casolini, Paola; Venerosi, Aldina; Alemà, Giovanni Sebastiano; Nicoletti, Ferdinando; Calamandrei, Gemma
Abstract: Perinatal hypoxia causes long‐term neurobiological consequences, including alterations in mechanisms of activity‐dependent synaptic plasticity and cognitive dysfunction. Changes in neurotransmitter receptors have been associated with these alterations, but little is known on how early hypoxia influences the expression and function of metabotropic glutamate (mGlu) receptors in adult life. This is an important issue because mGlu receptors are implicated in mechanisms of synaptic plasticity. Here, we examined the expression of mGlu1, mGlu5, and mGlu2/3 receptor subtypes in the hippocampus, nucleus accumbens, prefrontal cortex, and dorsal striatum in 6‐month old Wistar rats (a) born by vaginal delivery; (b) born by caesarean section; and (c) born by caesarean section followed by 20 min of asphyxia. Unexpectedly, we found a large reduction of mGlu1α protein levels in the hippocampus of rats born by caesarean section regardless of the presence of asphyxia. No changes in mGlu1α receptor protein levels were found in the other brain regions. Levels of mGlu5 and mGlu2/3 receptors and levels of GluA2/3 and GluN1 subunits of AMPA and NMDA receptors did not differ among the three groups of rats in any brain region. These results are consistent with previous findings showing that changes in mGlu1 receptors occur within the epigenetic programming caused by early‐life events. Abstract : Perinatal hypoxia causes long‐term neurobiological consequences. Here, we examined different glutamate subtype receptors in the hippocampus, nucleus accumbens, prefrontal cortex and dorsal striatum in adult rats born by vaginal delivery, caesarean section, and caesarean section followed by asphyxia. Unexpectedly, we found that caesarean delivery by itself caused a selective reduction of mGlu1α receptors in the hippocampus but not in the other brain regions. Levels of mGlu5, mGlu2/3, GluA2/3 and GluN1 receptors did not differ among the three groups in any brain region. These results demonstrated that changes in mGlu1 receptors occur within the epigenetic programming caused by early‐life events.